2022
DOI: 10.1111/rssa.12942
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Establishment Survey Non-Response Using Administrative Data and Machine Learning

Abstract: Declining participation in voluntary establishment surveys poses a risk of increasing non‐response bias over time. In this paper, response rates and non‐response bias are examined for the 2010–2019 IAB Job Vacancy Survey. Using comprehensive administrative data, we formulate and test several theory‐driven hypotheses on survey participation and evaluate the potential of various machine learning algorithms for non‐response bias adjustment. The analysis revealed that while the response rate decreased during the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Conversion rates were low and did not differ significantly by the type of email invitation. This was expected as low response is common in voluntary business surveys, especially when compared to mandatory government surveys (Küfner, Sakshaug, and Zins 2022). This research found that larger firms had higher conversion rates than smaller firms.…”
Section: Discussionmentioning
confidence: 62%
“…Conversion rates were low and did not differ significantly by the type of email invitation. This was expected as low response is common in voluntary business surveys, especially when compared to mandatory government surveys (Küfner, Sakshaug, and Zins 2022). This research found that larger firms had higher conversion rates than smaller firms.…”
Section: Discussionmentioning
confidence: 62%